PENGARUH MODAL KERJA DAN PENDAPATAN USAHA TERHADAP LABA BERSIH PERUSAHAAN PADA PT. FAJAR ADHISURYA PERKASA - Irsan Anshari dan Safri M (Fakultas Ekonomi Universitas Borobudur, 2016)
PT. Fajar Adhisurya Perkasa engaged in construction services, engineering services and trade, to be able to compete globally and provide added value to the environment. in a business activity (business) run by PT. Dawn Adhisurya Perkasa. The company wants an optimal profit on its business, because each owner wants the capital invested in his business immediately quickly return and also the results of the capital invested so as to provide additional capital (new investment) and prosperity for the owner and all his employees. in maintaining its business PT. Dawn Adhisurya Perkasa, by managing the company's finances carefully and well-planned by working capital efficiency, will be able to increase business income, and increase net income.Financial accounting is a process that ends in the preparation of financial statements concerning the company as a whole for use by both internal and external parties, including working capital which is an investment company in short-term assets such as cash, securities (letters, securities), accounts receivable and inventory, with the fulfillment of working capital, the company will be able to maximize its profit. Revenue is the gross inflows of economic benefits arising from the normal activities of the enterprise if inflows result in an increase in equity that does not arise from the contribution of investment. Expense is a decrease in the economic benefits during an accounting period in the form of an outflow or decrease in assets or the occurrence of an obligation resulting in a division to the investor, while net income is the profit of the ongoing business after interest and taxes. Keywords : Working Capital snd Business Revenues Against Net Income